Differentiated serum levels of Krüppel-like factors 2 and 4, sP-selectin, and sE-selectin in patients with gestational diabetes mellitus - Hongmei Zhang#; Zhigao Chen#; Xiaoling Wang (Taylor & Francis Group, 2022)
Objectives This study aims to determine serum levels of human Krüppel-like factors (KLFs), sP-selectin and sE-selectin and establish correlations between them in patients with gestational diabetes mellitus (GDM).Methods Twenty-six GDM patients aged between 22 and 35 years and 25 healthy pregnant women aged between 23 and 34 years were recruited. Maternal serum levels of KLF2, KLF4, and their target proteins sP-selectin, sE-selectin were measured using enzyme-linked immunosorbent assays at 24-28 weeks of gestation.Results Women with GDM had significantly lower serum KLF2 than controls. However, the differences in levels of serum KLF4 between the control and GDM groups were not significant. Additionally, elevated serum sP-selectin and sE-selectin were found in the GDM group and not in the healthy group. Importantly, we also found that serum KLF2 levels were negatively correlated with indicators of glucose metabolism, including insulin, fasting blood glucose, 1-h oral glucose tolerance test, and glycated hemoglobin.Conclusion We conclude that (i) serum KLF2 might be indicative of GDM risk, and (ii) sP-selectin and sE-selectin were increased in GDM patients.